Transient Global Amnesia (TGA): Influence of Acute Hypertension in Patients Not Adapted to Chronic Hypertension - Rogalewski, Andreas; Beyer, Anne; Friedrich, Anja; Plümer, Jorge; Zuhorn, Frédéric; Greeve, Isabell; Klingebiel, Randolf; Woermann, Friedrich G.; Bien, Christian G.; Schäbitz, Wolf-Rüdiger (Frontiers in Neurology, 2021)
Objective: Transient global amnesia (TGA) is defined by an acute memory disturbance of unclear etiology for a period of less than 24 hours. Several studies showed differences in vascular risk factors between TGA compared to transient ischemic attack (TIA) or healthy controls with varying results. This retrospective and cross-sectional study compares the cardiovascular risk profile of TGA patients with that of acute stroke patients. Methods: Cardiovascular risk profile and MR imaging of 277 TGA patients was retrospectively analysed and compared to 216 acute ischemic stroke patients (26% TIA). Results: TGA patients were significantly younger and predominantly female compared to stroke patients. 90.6% of TGA patients underwent MRI, 53% of those showed hippocampal diffusion-weighted imaging (DWI) lesions. Scores for cerebral microangiopathy were lower in TGA patients compared to stroke patients. After statistical correction for age, TGA patients had higher systolic and diastolic blood pressure, higher cholesterol levels, lower HbA1c as well as blood glucose levels, and lower CHA2DS2-VASc scores. Stroke patients initially displayed higher CRP levels than TIA and TGA patients. TGA patients without DWI lesions were older and showed higher CHA2DS2-VASc scores compared to TGA patients with DWI lesions. Conclusion: This study revealed significant differences between TGA and stroke patients in regard to the cardiovascular risk profile. Our main findings show a strong association between acute hypertensive peaks and TGA in patients not adapted to chronic hypertension, indicating a vascular cause of the disease.